IMU jerk grab detection in snowboard freestyle - Friedl, F.; Gorges, T.; Merz, C. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
In freestyle snowboarding the grab length during tricks is of high interest for judging and therefore also in coaching athletes. Purpose of this study was to assess the detectability of grabs in snowboard freestyle tricks using jerk data of a board-attached IMU. 117 tricks performed on a trampoline by eight elite national team riders and one coach were analysed. In 95 / 117 jumps different grab phases could be detected using the jerk. The start (median = 0.01s, IQR = 0.01s) and end (median = 0.01s, IQR = 0.01s) of a grab phase, defined as first and last touch of the hand to the board, was more accurately detected than a stable grab position, defined as a locked hand-board phase during the grab without any further hand motion, at the start (median = -0.03s, IQR = 0.04s) and end (median = 0.05s, IQR = 0.03s). Conclusively, the jerk could precisely detect grab phase events in 95 of 117 jumps and therefore qualifies as coaching tool. To be eligible as a judging tool further studies should try to improve detection reliability by using different parameters or technologies and investigate on-snow suitability.